Pleomorphism and Viability of the Lyme Disease Pathogen Borrelia burgdorferi Exposed to Physiological Stress Conditions: A Correlative Cryo-Fluorescence and Cryo-Scanning Electron Microscopy Study - Vancová, Marie; Rudenko, Nataliia; Vaněček, Jiří; Golovchenko, Maryna; Strnad, Martin; Rego, Ryan O. M.; Tichá, Lucie; Grubhoffer, Libor; Nebesářová, Jana (Frontiers in Microbiology, 2017)
To understand the response of the Lyme disease spirochete Borrelia burgdorferi exposed to stress conditions and assess the viability of this spirochete, we used a correlative cryo-fluorescence and cryo-scanning microscopy approach. This approach enables simple exposition of bacteria to various experimental conditions that can be stopped at certain time intervals by cryo-immobilization, examination of cell viability without necessity to maintain suitable culture conditions during viability assays, and visualization of structures in their native state at high magnification. We focused on rare and transient events e.g. the formation of round bodies and the presence of membranous blebs in spirochetes exposed to culture medium, host sera either without or with the bacteriologic effect and water. We described all crucial steps of the workflow, particularly the influence of freeze-etching and accelerating voltage on the visualization of topography. With the help of newly designed cryo-transport device, we achieved greater reproducibility.